Kemanan Obat Biosimilar Trastuzumab dan Pertuzumab untuk Penyakit Kanker Payudara HER-2 Positif: Literature Review - Fikri Aldebaran Azizi; Salman Salman (Jurnal Sehat Mandiri, 2024)
A biosimilar is a biological product that is similar to the original reference product in terms of safety, purity, efficacy, with no clinically significant differences. Breast cancer is a dangerous disease that still claims the lives of many women in the world, which requires effective treatment to improve patient prognosis. With biosimilar treatment alternatives, it is important to evaluate their safety and effectiveness. This makes biosimilars convenient for patients who lack the high cost of cancer treatment. The analysis showed that the biosimilar drugs trastuzumab and pertuzumab had consistent performance and comparable efficacy to the reference drugs. The purpose of this article is to provide insight into the comparison of safety and effectiveness of trastuzumab and pertuzumab biosimilars against HER2-positive breast cancer with the reference product. The method used is a qualitative method by analyzing 10 articles that meet the eligibility of 1,405 literature found in PubMed. The conclusion of this literature review is that biosimilar pertuzumab and trastuzumab have good safety and effectiveness and are similar to their reference patent products. Although it has side effects such as nausea, thrombocytopenia, diarrhea and anemia. Which if combined with other drugs can add to the survival of patients and have an effect.